Initialization of a spin qubit in a site-controlled nanowire quantum dot. (16th May 2016) - Lagoudakis, Konstantinos G; McMahon, Peter L; Fischer, Kevin A; Puri, Shruti; Müller, Kai; Dan Dalacu,; Poole, Philip J; Reimer, Michael E; Zwiller, Val; Yamamoto, Yoshihisa; Vučković, Jelena
Abstract: A fault-tolerant quantum repeater or quantum computer using solid-state spin-based quantum bits will likely require a physical implementation with many spins arranged in a grid. Self-assembled quantum dots (QDs) have been established as attractive candidates for building spin-based quantum information processing devices, but such QDs are randomly positioned, which makes them unsuitable for constructing large-scale processors. Recent efforts have shown that QDs embedded in nanowires can be deterministically positioned in regular arrays, can store single charges, and have excellent optical properties, but so far there have been no demonstrations of spin qubit operations using nanowire QDs. Here we demonstrate optical pumping of individual spins trapped in site-controlled nanowire QDs, resulting in high-fidelity spin-qubit initialization. This represents the next step towards establishing spins in nanowire QDs as quantum memories suitable for use in a large-scale, fault-tolerant quantum computer or repeater based on all-optical control of the spin qubits.